Length–weight and length–length relations of twenty-three freshwater fish species (Actinopterygii) from the Yuanjiang River, Yunnan Province, China - Yaqiu Liu; Chendong He; Mingdian Liu; Weitiao Chen; Yuguo Xia; Yuefei Li; Shuli Zhu; Jie Li; Xinhui Li (Acta Ichthyologica et Piscatoria)
The length–weight (LWR) and length–length (LLR) relations of 23 species of native freshwater fishes of six families and three orders collected from the Yuanjiang River in the upper reaches of the Red River were analyzed. From June 2023 to October 2024, specimens representing 23 freshwater fish were obtained: Cyprinus rubrofuscus Lacepède, 1803; Placocheilus caudofasciatus (Pellegrin et Chevey, 1936); Poropuntius krempfi (Pellegrin et Chevey, 1934); Microphysogobio yunnanensis (Yao et Yang, 1977); Abbottina rivularis (Basilewsky, 1855); Opsariichthys bidens Günther, 1873; Hemibarbus medius Yue, 1995; Onychostoma gerlachi (Peters, 1881); Rasbora atridorsalis Kottelat et Chu, 1988; Schistura macrotaenia (Yang, 1990); Schistura fasciolata (Nichols et Pope, 1927); Vanmanenia tetraloba (Mai, 1978); Beaufortia leveretti (Nichols et Pope, 1927); Sinogastromyzon tonkinensis Pellegrin et Chevey, 1935; Bagarius rutilus Ng et Kottelat, 2000; Glyptothorax quadriocellatus (Mai, 1978); Glyptothorax honghensis Li, 1984; Glyptothorax interspinalum (Mai, 1978); Hemibagrus pluriradiatus (Vaillant, 1892); Pseudobagrus kyphus Mai, 1978;Tachysurus fulvidraco (Richardson, 1846); Tachysurus virgatus (Oshima, 1926); and Channa gachua (Hamilton, 1822). The total length (TL), standard length (SL), and body weight (BW) were determined for each fish individual to the nearest 0.1 cm and 0.1 g, respectively. All LLR and LWR parameters of 23 fish species were statistically significant (P < 0.001). The length–weight relations of 17 species have not previously been available in FishBase. Moreover, we provided a new distribution record of fish (Rasbora atridorsalis). Our study provided LWR values for the first time, which will help validate the accuracy and predictability of Bayesian models in estimating species-specific growth parameters for data-poor species. The majority of the LWR relations obtained in this study are new to this region. The availability of species- and region-specific data on length–weight relations could help inform future research and management of these species.